Ultrasound-Guided Aspiration Does Not Reduce the Recurrence Rate of Ganglion Cysts of the Wrist - Kurkis, Gregory; Anastasio, Albert; DeVos, Marijke; Gottschalk, Michael B. (Journal of Wrist Surgery, 2019)
Background Ganglion cysts are the most frequent soft tissue tumor encountered in the upper extremity and are commonly treated by aspiration or by surgical excision. Ultrasound is a promising addition to traditional aspiration, as it allows for visualization of the needle within the ganglion before aspiration.Questions Are ganglion cysts of the wrist less likely to reoccur if they are aspirated under ultrasound guidance versus “blind” aspiration without the use of ultrasound guidance? Does patient functionality change based on whether or not the cyst recurred?Patients and Methods In total, 52 patients were successfully contacted and recurrence rates were compared between those whose cyst was treated with ultrasound-guided (13 patients) with those whose cyst was treated with blind aspiration (39 patients). Mean follow-up time was 2.9 years.Results Recurrence rates were 69% (9 patients) and 74% (29 patients) for the ultrasound-guided and blind aspiration groups, respectively (p-value: 0.73), showing no significant difference in recurrences of wrist ganglion between the two groups. A metric of functionality (Quick–DASH [Disabilities of the Arm, Shoulder, and Hand]) revealed worse outcomes in patients who experienced return of ganglion cyst after aspiration versus those who did not.Conclusion Additional studies with improved sample sizes are needed to demonstrate the superiority of ultrasound-guided aspiration versus blind aspiration. Due to a high recurrence rate following aspiration (both ultrasound-guided and blinded), a lower threshold for surgical intervention is likely reasonable.Level of Evidence This is a Level IIIb study.
Keywords: ganglion cyst; ultrasound; recurrence; volar; dorsal